2021
DOI: 10.3390/biology10020078
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Tissue Expression Pattern of Zebrafish CRP-Like Molecules Suggests a Relevant Antiviral Role in Fish Skin

Abstract: Recent studies suggest that short pentraxins in fish might serve as biomarkers for not only bacterial infections, as in higher vertebrates including humans, but also for viral ones. These fish orthologs of mammalian short pentraxins are currently attracting interest because of their newly discovered antiviral activity. In the present work, the modulation of the gene expression of all zebrafish short pentraxins (CRP-like proteins, CRP1-7) was extensively analyzed by quantitative polymerase chain reaction. Initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 75 publications
1
2
0
Order By: Relevance
“…As in humans, at least some of the zebrafish Crp isoforms seem to be acute phase proteins since their expression is induced upon bacterial as well as viral infections [138,156,157]. In the case of crp2-1, this was also evident in our data.…”
Section: Plos Geneticssupporting
confidence: 79%
“…As in humans, at least some of the zebrafish Crp isoforms seem to be acute phase proteins since their expression is induced upon bacterial as well as viral infections [138,156,157]. In the case of crp2-1, this was also evident in our data.…”
Section: Plos Geneticssupporting
confidence: 79%
“…The authors also found that 11 of these TRIMs were significantly induced during grass carp reovirus (GCRV) infection and, by co-expression analyses, they identified three trim genes that could be considered as a part of the type I interferon response [ 3 ]. On the other hand, Bello-Perez et al [ 4 ] analyzed the expression of the seven C-reactive proteins (CRPs) previously identified in zebrafish ( Danio rerio ) under basal conditions and after spring viraemia of carp virus (SVCV) infection in different tissues. Most of these crp genes were altered after the viral challenge in different tissues, including the skin.…”
mentioning
confidence: 99%
“…Most of these crp genes were altered after the viral challenge in different tissues, including the skin. This tissue also showed a higher expression of these genes in the recombinant activation gene 1 ( rag1 ) mutant zebrafish compared to their wild-type counterparts, suggesting an overcompensation of the innate immune in the absence of the adaptive one [ 4 ]. Finally, Pereiro et al [ 5 ] analyzed by RNA-Seq the repertoire of long non-coding RNAs (lncRNAs) in the brain and head kidney from European sea bass ( Dicentrarchus labrax ) and identified those lncRNAs significantly modulated after infection with nodavirus.…”
mentioning
confidence: 99%